1987
DOI: 10.1016/s0006-3495(87)83251-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements of intra- and extracellular Na+ and water in the brain and muscle by nuclear magnetic resonance spectroscopy with shift reagent

Abstract: The introduction of new paramagnetic shift reagents in the nuclear magnetic resonance (NMR) method has made it possible to distinguish intra- and extracellular ions in tissues or organs in vitro. We measured the intra- and extracellular 23Na and 1H in vivo in the gerbil brain and skeletal muscle by NMR spectroscopy employing the shift reagent, dysprosium triethylenetetraminehexaacetate (Dy[TTHA]3-). Without Dy(TTHA)3-, the 23Na and 1H signals were seen only as single peaks, but gradual intravenous infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 21 publications
(28 reference statements)
1
40
1
Order By: Relevance
“…Our measurements of the permeability of the normal BBB to DylTHA'-do not support the proposal of Naritomi et al 13 that this shift reagent can be applied in conjunction with in uiuo 23Na NMR spectroscopy of the brain to distinguish between intra-and extracellular Na'. To obtain a minimally adequate shift of 3 4 ppm in the resonance frequency of extracellular Na' would require an interstitial concentration of DyTI'HA3-of 7-9 mM."…”
Section: Ks Post Ischemiacontrasting
confidence: 99%
“…Our measurements of the permeability of the normal BBB to DylTHA'-do not support the proposal of Naritomi et al 13 that this shift reagent can be applied in conjunction with in uiuo 23Na NMR spectroscopy of the brain to distinguish between intra-and extracellular Na'. To obtain a minimally adequate shift of 3 4 ppm in the resonance frequency of extracellular Na' would require an interstitial concentration of DyTI'HA3-of 7-9 mM."…”
Section: Ks Post Ischemiacontrasting
confidence: 99%
“…In essence, the exchange of water between the two compartments provides an additional relaxation pathway for intracellular water. Indeed, in the limit at which the exchange process completely overwhelms the inherent spin-lattice relaxation process, i.e., when [2] the observed relaxation time for intracellular water is identically the exchange lifetime, [3] In what follows, we show for a perfused, microbead-adherent HeLa cell system that: (i) the apparent relaxation of extracellular water is dominated by flow effects, (ii) the apparent relaxation is sufficiently rapid to completely suppress signal from extracellular water, (iii) the intracellular longitudinal relaxation is slow relative to exchange of water between the intracellular and extracellular compartments, being nearly described by Eq. [3], and, thus, (iv) this method, when combined with an inversion recovery pulse sequence, yields the intracellular water lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, application of pure theory to understanding DY(TTHA)-~ effects on the brain is extremely complex. Because of this complexity and despite the agreement that the electrical charges on DYTTHA-~, (in which TTHA is covalently bound to dysprosium), prevents movement of DY(TTHA)-~ across the BBB or into the intracellular space, controversy exists over the ability of DY(TTHA)-~ to distinguish between Viv, Vi, and Vic (4)(5)(6)(7). Much of this controversy has to do with the relative contributions of shifts from hyperfine (Ah) interactions versus bulk magnetic susceptibility effects (Ax) (7).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the physiologicall y well tolerated paramagnetic shift reagent dysprosiurn(II1)triethylenetetraminehexacetate DY(TTHA-~) (2) allows the possibility of performing 23Na MRS measurements of compartmentally resolved sodium (3). Naritomi et al (4,5) reported separation of intracellular and extracellular Na+ and water in the brain using DYTTHA-~. However, their assignment of specific compartments to specific peaks in the 23Na NMR spectra has been questioned (6, 7).…”
Section: Introductionmentioning
confidence: 99%